1992
DOI: 10.1063/1.107303
|View full text |Cite
|
Sign up to set email alerts
|

Optical absorption in plasma-deposited silicon oxynitride films

Abstract: We present an experimental and theoretical study of the optical absorption of amorphous silicon oxynitride films. The optical absorption coefficient α in the energy range from 4 to 10 eV has been measured for SiOxNyHz films between the nitride and oxide compositions grown by plasma-enhanced chemical vapor deposition. We have also calculated the coefficient α for SiOxNy alloys assuming a random mixture of Si—N and Si—O bonds within the disordered alloy. The variation of the optical gap Eg with the composition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…Such an absorption is absent in silica glass. As Si–N groups are known to have UV absorption, the significant reduction in the UV absorption can be attributed at first glance to the decrease in Si–N bonds. It should be noted, however, that the UV absorption remained even in the film exposed for 24 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such an absorption is absent in silica glass. As Si–N groups are known to have UV absorption, the significant reduction in the UV absorption can be attributed at first glance to the decrease in Si–N bonds. It should be noted, however, that the UV absorption remained even in the film exposed for 24 h (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our observed orange emission bands at 2 eV (DL1) and 2.16 eV (DL3) could have a similar origin. The slightly higher energy of DL3 band in sample SN3 may be associated with the higher O content and be explained as follows: Ance et al 24 reported that for the SiO x N y films, which are assumed to have a random mixture of Si-N and Si-O, the bottom of the conduction band shifts to higher energy while the valence band maximum does not change. Thus, the optical gap opens with increasing oxygen content, as compared to the original band gap of Si 3 N 4 .…”
Section: B Photoluminescence Propertiesmentioning
confidence: 99%
“…The elliptically polarized photoinduced second harmonic generation (PISHG) in SiN x O y films [18] was studied for specimens with different nitrogen to oxygen (N/O) ratios. The theoretical and experimental study of the optical absorption of amorphous plasma deposited SiON films along with the variation of the optical gap E g with respect to the composition and the appearance of the steps in the optical absorption for oxygen-rich samples have been reported by Ance et al [19]. The growth of high quality ultrathin oxynitride films, formed by nitridation of SiO 2 in nitric oxide ambient, using in Situ rapid thermal processing have been reported for the use of CMOS and EEPROM technologies by Bhat et al [20].…”
Section: Introductionmentioning
confidence: 96%